Study of Correlation of Dental Age with Radiological Age - Sharad V. Kuchewar; Trishul O. Padole; Santosh H. Bhosle; Anil K. Batra (Institute of Medico-legal Publications Pvt Ltd, 2021)
Age is defined as the length of time an organism or individual has survived after birth. Age assessment is necessary for people without birth registrations, getting access to education, government policies, employment, marriage registration, young criminals claiming to be underage, and so on. Under 25 years of age, following parameters are key factors to opine about age of individual - Dental eruption, Bone size and maturity, ossification centre & epiphysial union. Aim of the study was age determination by Correlation of Dental findings with Radiological findings. This study included 83 individuals brought by police to SVN Govt. Medical college, Yavatmal, for age determination, out of them 56 were males and 27 were females between age group of 10-25 years. The oral cavity was examined for dentition as per Federation Dentaire Internationale (F.D.I.) system. X-rays of the body joints are recommended for determining the age groups. The results obtained were compared with reference value available for same parameter, for standard deviation, Pearson correlation and p values. Very strong correlation found between Radiological age and Final age (0.9994) while correlation between Dental age and Radiological age was 0.9961. Concluded highly significant p-value (p<0.0001) found between Dental, Radiological and Final age.